The Dynamics of Green Bond Effectiveness in Achieving Sustainable Development: A Comparative Study with a Scoping Review Approach - Istiqomah Nur Barokah; Bandiyono, Agus (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2025)
The implementation of environmental, social, and governance (ESG) principles integrated into business practices and public policies is a strategic step in realizing the 2030 Sustainable Development Goals (SDGs). However, this effort requires a lot of funding. To overcome these challenges, countries around the world have created innovative funding instruments specifically aimed at developing green projects, namely green bonds. The comparative study conducted used the scoping review method to assess the effectiveness of green bond issuance in various countries, identify challenges, and review various recommendations for the development of green bonds. The results of the study show that green bond issuance is still concentrated in certain sectors, such as energy and environmentally friendly building construction. Obstacles to green bond development vary from country to country, including aspects of issuance, regulation, and investor appeal. The articles referenced in this study comprehensively discuss the potential, benefits, challenges, and recommendations to maximize the role of green bonds as a sustainable funding solution.